Alternative production of pro-death Bax∆2 protein via ribosomal frameshift in Alzheimer’s disease - Qi Yao; Adriana Mañas; Evan Beatty; Anne Caroline Mascarenhas dos Santos; Yi Zhou; Oscar Juárez; Hui Chen; Jialing Xiang (Scientific Reports)
Abstract Pro-death Bax family member, Bax∆2, forms protein aggregates in Alzheimer’s disease neurons and causes stress granule-mediated neuronal death. Production of Bax∆2 originated from two events: alternative splicing of Bax exon 2 and a microsatellite mutation (a deletion from poly guanines, G8 to G7). Each event alone leads to a reading frameshift and premature termination. While Bax exon 2 alternative splicing is common in Alzheimer’s brains, the G7 mutation is not, which is inconsistent with the high Bax∆2 protein levels detected in clinical samples. Here, we report an alternative mechanism to produce Bax∆2 protein in the absence of the G7 mutation. Using dual-tag systems, we showed that a ribosomal frameshift (RFS) can compensate the lack of G7 mutation in translating Bax∆2 protein. Intriguingly, the microsatellite poly G repeat is neither essential nor the site for the RFS. However, disruption of the poly G sequence impaired the RFS, potentially due to alteration of the local RNA structure. Using immunoprecipitation-mass spectrometry, we pinpointed the RFS site at 15 base pairs upstream of the microsatellite. These results uncover an alternative mechanism for generating functional Bax∆2-subfamily isoforms, highlighting the production plasticity of Bax family isoforms and unveiling potential new therapeutic targets for Alzheimer’s disease.